Male victims of domestic violence among professional families: Shackled in masculinity - Mas'udah, Siti (Jurnal Sosiologi Dialektika, 2024)
Various acts of domestic violence are the reality that troubles family life in various social classes. This study seeks to investigate violence experienced by men among professional families and the causes of women to commit such act. This study deployed qualitative methods and conducted in-depth interviews of 53 informants. The finding of the study indicates that men not only experience single violence, but a variation of violence that occurred in professional families, such as physical, economic, verbal/psychological, and sexual violence. This study shows the triggers for women to commit violence against men among professional families are insecurity, jealousy, and inequality in socioeconomic status. Men are burdened with patriarchy and tend to be passive in reacting to the violence they experience. Masculinity makes male victims of violence suffer triple oppression: They become the victims; they are embarrassed because they get a negative stigma from the community for failing and not being able to lead their families; and when men become the victims, they ‘get punished' because it is considered as ‘abnormal' for men to become victims of violence. Men react to the violence committed by their wives by carrying out latent resistance, manifest resistance, and alienation.